Acute retinal necrosis: diagnostic and treatment strategies in Germany - Winterhalter, Sibylle; Mackensen, Friederike (Ocular immunology and inflammation, 2016)
Purpose: To analyze the preferred practice respective diagnosis, treatment, and complications in patients with acute retinal necrosis in Germany.Methods: The uveitis-section of the German Ophthalmologic Society developed a questionnaire with 12 questions concerning patients with acute retinal necrosis seen in the 5 years up to August 2009.Results: In total, 35 eye hospitals answered the questionnaire and reported 213 patients with acute retinal necrosis. Diagnosis was made clinically in 86%. Anterior chamber tap, vitreous biopsy, diagnostic vitrectomy, and serology were performed for confirmation. Therapy was started with acyclovir in all institutions, and continued with ganciclovir, foscarnet and brivudine in some cases. Intravitreal injections were performed in 46%. Additional oral steroids were given in 80%. A following oral antiviral treatment was performed in 94%.Conclusions: Relevant variations were seen in diagnosis and treatment practices. The survey outlines the need for a unique diagnostic and therapeutic guideline.